Práticas pedagógicas de professores da educação matemática num contexto de formação continuada em modelagem matemática na educação matemática - Mutti, Gabriele de Sousa Lins (2016)
The increase of debates about the Mathematical Modeling, as a research area and a pedagogical possibility for the classroom, has been ratified by numerous researches in the scope of Mathematics Education. Although a discourse of apology to the insertion of Modeling into the pedagogical practice of Mathematics teachers echoes around the country, this has being occurred on a beginner basis. There are authors in the Mathematics Education community who associate this condition with the need to insert teachers in training contexts, which effectively enable them to incorporate this tendency into their daily practice. In this sense, a model of Continuing Education for Teacher in Mathematical Modeling at Mathematical Education was established, similar (but not identical) to that established by "C. M. Garcia". This model is configured as an inspection sub region on which we intentionally moved. From this movement raised a question: What is revealed about the pedagogical practices of teachers of the Basic Education, members of the Continuing Education for Teacher in a Mathematical Modeling at Mathematical Education?" that was constituted as a guide of this investigation, assumed from a phenomenological perspective. As we pursued it we saw the possibility to investigate the pedagogical practices of the member teachers in two aspects: discourse and action. In order to do so, the gathering of the materials which were constituted a research data took place in two different scopes: the meetings of the Continuing Education and the classrooms of these teachers. In the scope of the meetings, we looked at what the eleven member teachers said orally or textually from November 2015 to July 2016, total of fourteen meetings. We also went to the classrooms of eight of these teachers and observed eight classes of each one of them. After the collection and transcription of the materials, we moved on to the process of analysis and interpretation that was optimized by Atlas.ti software. All the collected materials were analyzed together, without a teacher-teacher separation. We began by highlighting from the transcripts text the excerpts that were convergent to our question, aiming to constitute units of meaning. From this analysis, four open categories emerged, which were described and interpreted from a phenomenological hermeneutical movement. Interpretations revealed, among other things, that the pedagogical practices of the member teachers have a plural character that provides indications, both from a movement of rupture with the traditional model of Mathematics teaching, and from a disposition to the adoption of Modeling. For this adoption to take place, however, it is necessary that exist socio-epistemological-formative conditions that ensure the impulse and permanence of these teachers in this new style of work. In addition, interpretations make explicit that the Continuing Education in Modeling should be flexible and shared, so that it can receive teachers respecting their different levels of appropriation in relation to Modeling, stimulating them to move forward and establishing a common environment - the constitution of a collective in Modeling - that allows the strengthening of an understanding among its members about Modeling as a possible practice.